Molar Pregnancy and Its Associated Risk Factors: A Case-Control Study in Qazvin, Iran - Niloofar Alimohammadi; Hamideh Pakniat; Monirsadat Mirzadeh; Ali Emami; Ahmadreza Vasheghani Farahani (Fasa University of Medical Sciences, 2021)
Background & Objective: Hydatidiform Mole (HM) is a type of gestational trophoblastic disease which causes serious complications and recognizing risk factors can play an important role in reducing the incidence. The aim of this study is to evaluate HM risk factors in Kowsar hospital in Qazvin, Iran. Materials & Methods: In this case-control study, 77 pregnant women, by complete enumeration method with sonographic and pathological diagnosis of molar pregnancy in Qazvin Kowsar hospital in 2016-2017, were assigned to the case group and 77 pregnant women with no delivery problems were assigned to the control group. All demographic and midwifery data were extracted from the records in the hospital archive. Before patients were enrolled in this study, written consent was obtained. Data were analyzed by t-test and chi-square in SPSS software version 22. P<0.05 was considered significant. Results: Mean age in both case and control groups was 27.16 ± 7.26. There was no significant difference in preeclampsia, multiple pregnancy, blood groups, Rhesus (Rh) and contraceptive methods in case and group groups (P>0.05). There was a significant relationship between HM and history of molar pregnancy and multiparity (OR: 2.1; CI: 1.77-2.48; p=0.01, OR: 1.85; CI: 1.07-3.6: p=0.04). Conclusion: The present study also showed that HM was more likely to occur in multipara patients and patients with history of molar pregnancy. Therefore, it is recommended that women should undergo health care before pregnancy and further studies are required to provide solutions to reduce the cases of HM.